The Effect of English Audio Visual Towards Students’ English Listening Skill - Fatimah Windi Yana; Yugi Dirada Prawiyata; Rini Fadhillah Putri; Ahmad Laut Hasibuan (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2022)
The objective of the research was to find out whether there is significant effect of using media audio visual on students’ competency in listening skill. This research was conducted in MAS AL-MANAR Medan students of tenth grade. This research used quantitative research with experimental design with two classes. Control class consisted of 20 students and experimental class consisted 21 students. This research used media audio visual as learning method. The technique of collecting data of this research were pre-test, treatment, and post-test. With each test comes 10 questions of multiple choice. The results obtained in this research proved that there was a different score on students’ in learning listening by using media audio visual and used media audio. Students’ achieved good grades but in the control class it was lower than the experimental class. It could be show as follows that the t-test value was 14.735 with df= n-2 = 39, tobserved >ttable, tobserved was higher than ttable with 2.0227. It can be concluded that Media Audio Visual can be affected on students’ listening skill.